Measurements of current-use pesticides and oxidation products using chemical ionization mass spectrometry - Murschell, Trey Daniel, author; Farmer, Delphine K., advisor; Borch, Thomas, committee member; Kennan, Alan, committee member; Collett, Jeffrey L., committee member (Colorado State University. Libraries, 2018)
Pesticides are both naturally occurring compounds found within a variety of plant species and also synthetic chemicals that are used to protect vulnerable organisms against disease carriers, harmful pests, and intrusive or undesirable vegetation. Pesticide use has large agricultural, economic, and health benefits which include increased staple food production, protection of susceptible ecosystems and wetlands, increased productivity of the labor force via disease control, and the creation of a booming chemical industry. In the decades following the discovery of DDT's anti-insecticidal properties, organochlorine pesticides (OCPs) were generously applied across the globe. OCPs appeared to have low toxicity to mammals, chiefly humans, but had adverse effects to non-target species like fish and predatory birds. OCPs persisted in soil, air, and water, and were transported atmospherically, as far as the Arctic. The prohibition of OCPs by most nations spurred research into less harmful and persistent pesticides. These current-use pesticides (CUPs) have mostly replaced OCPs and are applied world-wide. However, recent studies revealed the transport of CUPs to remote areas, including isolated Pacific islands, high alpine mountain lakes, and, again, the Arctic. Once in the atmosphere, these pesticides undergo physical and chemical processes that affect atmospheric lifetimes and transport, and potentially change the toxicity of the parent pesticides, which can have unforeseen impacts on sensitive ecosystems and organisms. With pesticide use perpetually linked to negative health questions and concerns, atmospheric monitoring, understanding of chemical processes, and improving analytical methods is necessary. Presented in this dissertation is work towards understanding pesticides and their chemistry in the atmosphere using real time mass spectrometry. A new calibration and measurement method for four CUPs, atrazine, metolachlor, permethrin, and trifluralin is shown in Chapter 2. Iodide chemical ionization mass spectrometry (CIMS) offers a real-time, sensitive measurement technique for herbicides, as well as other low volatility species. Presented in Chapter 3, ambient pesticide spray volatilization and post-application volatilization of two chlorophenoxy acid herbicides, 2,4-D and MCPA, were measured using acetate CIMS. Concentrations of 2,4-D were highest during the application period, while MCPA concentrations increased with increasing ambient temperature. Henry's Law constants and vapor pressure were found to be predictors for spray volatilization and post-application volatilization, respectively. OH radical chemistry of three aromatic herbicides are presented in Chapter 4, along with proposed oxidation mechanisms and products. Experiments were performed in an Oxidative Flow Reactor (OFR) coupled to a switching reagent ion CIMS, for a non-targeted approach for pesticide oxidation product detection. Pesticide oxidation followed typical OH oxidation mechanisms (OH abstraction with subsequent peroxide formation, OH addition to aromatic systems). MCPA and Mecoprop-p reaction rate constants with OH radical were estimated and used to calculate their atmospheric lifetimes (3 and 5 days, respectively). Newly identified products from MCPA and triclopyr oxidation are potentially harmful to the environment and to humans. Lastly, Chapter 5 covers oxidation of two nitrogen containing herbicides, trifluralin and acetochlor and mechanisms with proposed products are shown. Trifluralin photolyzed to produce NOx, and both herbicides produced isocyanic acid (HNCO) upon OH oxidation, an atmospheric toxin.
Keywords: chemical ionization mass spectrometry; atmospheric oxidation; pesticides